Rituximab for IgG4-related disease: a prospective, open-label trial. Issue 6 (9th February 2015) - Carruthers, Mollie N; Topazian, Mark D; Khosroshahi, Arezou; Witzig, Thomas E; Wallace, Zachary S; Hart, Philip A; Deshpande, Vikram; Smyrk, Thomas C; Chari, Suresh; Stone, John H
Abstract : Objectives: To evaluate the efficacy of rituximab (RTX) in IgG4-related disease (IgG4-RD) in an open-label pilot trial. Methods: We treated 30 IgG4-RD patients with two doses of RTX (1000 mg each). The participants were either treated with RTX alone (n = 26; 87%) or required to discontinue baseline glucocorticoids (GC) within 2 months (n = 4; 13%). Disease activity was measured by the IgG4-RD Responder Index (IgG4-RD RI) and physician's global assessment (PGA). Disease response was defined as the improvement of the IgG4-RD RI by two points. The primary outcome, measured at 6 months, was defined as: (1) decline of the IgG4-RD RI ≥2 points compared with baseline; (2) no disease flares before month 6; and (3) no GC use between months 2 and 6. Complete remission was defined as an IgG4-RD RI score of 0 with no GC use. Results: Disease responses occurred in 97% of participants. The baseline IgG4-RD RI and PGA values, 11±7 and 63±22 mm, respectively, declined to 1±2 and 11±16 mm at 6 months (both p<0.00001). The primary outcome was achieved by 23 participants (77%). Fourteen (47%) were in complete remission at 6 months, and 12 (40%) remained in complete remission at 12 months. Among the 19 with elevated baseline serum IgG4, IgG4 concentrations declined from a mean of 911 mg/dL (range 138–4780 mg/dL) to 422 mg/dL (range 56–2410 mg/dL) at month 6 (p<0.05). However, only 8 (42%) of the 19 achieved normal values. Conclusions: RTX appears to be an effective treatment for IgG4-RD, even without concomitant GC therapy. Trial registration number: ClinicalTrials.gov identifier: NCT01584388 .